Jurassic Paleomagnetic Data From the Eastern Tethyan Himalaya Support a Smaller Greater India - Jie Yuan; Chenglong Deng; Zhenyu Yang (Geophysical Research Letters)
Abstract Knowledge of the original dimension of Greater India in the Jurassic Period is critical for reconstructing the paleogeographic framework of Gondwana. However, two end‐member reconstructions for Greater India (≤1,000 or ≥2,000 km) exist in the Jurassic. Here, we conduct comprehensive petrographic, rock magnetic, and paleomagnetic studies on Lower to Middle Jurassic Lure Formation marlstones from the eastern Tethyan Himalaya. The new paleomagnetic data fulfill stringent quality criteria and provide a reliable Early Jurassic paleopole of 16.6°N/308.8°E, A95 = 1.2°, n = 396 (specimens), which constrains the Tethyan Himalaya to a paleolatitude of 31.8° ± 1.2°S at ca. 177.3 Ma. The overlap of this paleolatitude with the expected paleolatitude of India is consistent with a small Greater India (∼900 km) in the Jurassic. The improved estimate of the dimension of Greater India contributes to an updated reconstruction of the paleogeography of Gondwana during the Early Jurassic.